Method for strengthening anaerobic methanogenesis of high-solid-content sludge and reducing sludge resistance genes by anchoring nickel nanoparticles with nitrogen-doped nanofibers
By using nitrogen doped nanofiber to anchor nickel nanoparticles as conductive materials, the problem of poor treatment effects and low methane yield in the high -linked anaerobic digestion system, realized efficient methane generating and sludge resistance genes. And this material can be recycled and reused.
Patent Information
- Application Number
- CN202411712184.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing anaerobic digestive systems using conductive materials have poor treatment effects in high-solid-containing systems, low methane yield, and difficult to recover conductive materials, a single methane production promotion mechanism and limited increase.
The nitrogen doped nano-fiber anchor nickel nanoparticles as a new type of conductive material. It is prepared through solitary-gel method, electrostatic spinning, and thermal carbonization technology to strengthen high-lid mud and sanxitrodic oxygen. Sex genes.
It significantly increases the generating rate and cumulative yield of methane in high -linked sludge anaerobic digestion, reducing the content of sludge resistance genes, increasing the hydrolysis rate and organic degradation rate of the sludge, and recycling and reuse of conductive materials.
Smart Images

Figure CN119371067A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for treating high-solid-content excess sludge, and belongs to the field of solid waste treatment. Background Art
[0002] Since sludge contains a large amount of toxic, harmful and perishable pollutants, it will cause great damage to the environment and human health if not properly handled.
[0003] Anaerobic digestion has many advantages because it can harmlessly treat sludge while recycling resources, including reducing the amount of sludge, killing pathogenic microorganisms and recovering bioenergy in the form of methane. Therefore, it has become a popular sludge treatment technology. The total solid content of 15% (mass ratio) is usually used as the boundary to distinguish between high-solid anaerobic digestion systems (total solid content greater than 15%) and low-solid anaerobic digestion systems (total solid content less than 15%). Compared with the low-solid sludge anaerobic digestion system, the high-solid sludge anaerobic digestion system is considered to be a more feasible method due to its smaller reactor volume, low heating energy consumption, less sewage production, and high unit volume of biogas production.
[0004] In recent years, more and more studies have proposed adding conductive materials to anaerobic digestion systems to promote direct electron transfer between microbial species, so as to accelerate the rate of methane production and increase the cumulative methane production. Direct interspecies electron transfer directly transfers electrons from electron donors such as acidogenic bacteria to electron acceptors such as methanogens in a contact manner through the conductive cilia of microorganisms or extracellular conductive substances. Direct interspecies electron transfer has been proven to be more efficient than interspecies hydrogen transfer in terms of electron transfer rate and breaks through the thermodynamic barrier of acid production. However, traditional conductive materials are difficult to play a role in high-solid systems. Affected by the solid content of the system, it is difficult to quickly establish an efficient electron transfer rate between microorganisms after the addition of conductive materials, and energy transfer cannot be achieved. In addition, most of the existing conductive materials are difficult to recover from the fermented biogas slurry and biogas residue, and the methanogenesis promotion mechanism is relatively single, the methane increase is limited, and it is difficult to continuously, stably and efficiently play a role in improving methanogenesis. Summary of the invention
[0005] The present invention aims to solve the technical problems of poor treatment effect and low methane production of existing anaerobic digestion systems using conductive materials, and provide a method for strengthening anaerobic methanogenesis of high-solid sludge and reducing sludge resistance genes by anchoring nickel nanoparticles with nitrogen-doped nanofibers.
[0006] The method of the present invention using nitrogen-doped nanofibers to anchor nickel nanoparticles to enhance anaerobic methanogenesis in high-solid sludge and reduce sludge resistance genes is carried out in the following steps:
[0007] 1. Prepare nickel nanoparticle precursor by sol-gel method: dissolve nickel nitrate hexahydrate (Ni(NO3)2·6H2O) in a mixed solution of ethanol and water, add ammonia water to adjust the pH value to 9-11, stir at 100-120 rpm for 0.5-1 hour to hydrolyze to generate uniformly dispersed sol particles, and then stand for 4-6 hours to obtain nano nickel precursor by spontaneous gelation;
[0008] 2. Evenly dispersing the nano nickel precursor in a polyacrylonitrile solution with a mass percentage concentration of 10% to 16% and N,N-dimethylformamide (DMF) as a solvent to obtain an electrospinning solution; adding the electrospinning solution to an electrospinning machine for electrospinning to obtain primary nanofibers; and then vacuum drying the primary nanofibers to obtain nanofibers containing a nickel precursor;
[0009] 3. Place the nanofibers containing nickel precursor in a high temperature tube furnace at 10-15°C min -1 The heating rate is raised to 400-420℃ and kept at this temperature for 1-1.5h, then increased to 10-15℃ min -1 The heating rate is continued to be increased to 900-950°C and kept for 2-2.5 hours, and finally cooled to room temperature to obtain nitrogen-doped nanofiber-anchored nickel nanoparticles;
[0010] 4. Add high-solid sludge into an anaerobic digestion reactor, then inoculate anaerobic sludge, and then add nitrogen-doped nanofiber-anchored nickel nanoparticles; the headspace volume of the reactor is 20% to 25% of the effective volume of the reactor, and the amount of nitrogen-doped nanofiber-anchored nickel nanoparticles added is 5% to 12% of the dry weight of the high-solid sludge; continuously introduce nitrogen into the anaerobic digestion reactor to remove mixed oxygen in the system, and then operate the anaerobic digestion reactor at a temperature of 35 to 38°C, and the hydraulic retention time of the high-solid sludge in the anaerobic digestion reactor is 30 to 35 days, thereby completing the anaerobic methanogenesis of the high-solid sludge and the reduction of sludge resistance genes.
[0011] Furthermore, in the electrospinning described in step 2, the voltage of the electrospinning machine is 20 kV and the solution injection speed is 1.5 mL·h -1 , humidity is 25% to 30%, and the distance between the shaft rollers is 20cm.
[0012] Furthermore, the vacuum drying in step 2 is carried out under vacuum conditions at a temperature of 70 to 80° C. for 10 to 12 hours to remove the residual organic solvent;
[0013] Furthermore, the high-solid sludge in step 4 has a solid content of 16% to 20% by mass;
[0014] Furthermore, the main microorganisms in the anaerobic sludge in step 4 are Methanothrix, Methanobacterium and Methanolinea.
[0015] Furthermore, in the anaerobic sludge described in step 4, the abundance of Methanothrix in terms of mass percentage is 40% to 45%, the abundance of Methanobacterium in terms of mass percentage is 18% to 20%, and the abundance of Methanolinea in terms of mass percentage is 15% to 17%.
[0016] The present invention prepares a method for preparing a nitrogen-doped carbon nanofiber anchored nickel nanoparticle, and using this new conductive material to promote the anaerobic digestion of high-solid sludge to produce methane, which has the following main characteristics:
[0017] (1) Material preparation method and structural characteristics: The material is prepared by sol-gel method, electrospinning and pyrolysis carbonization technology. It has a fiber spiral winding structure and a large surface area, which is conducive to the attachment and growth of microorganisms. The surface contains a variety of functional groups, which promote the extracellular electron transfer of bacteria. Combined X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM / TEM) analysis confirmed the uniform distribution and stable loading of nitrogen functional groups and nickel nanoparticles. Oxidative stress detection showed that under the action of nickel nanoparticles, the level of reactive oxygen species (ROS) increased by 28.1-65.9%.
[0018] (2) Adsorption and inactivation of bacteriophages: The conductive material of the present invention has the ability to adsorb and inactivate bacteriophages. The surface of the material contains nickel nanoparticles with an average particle size of 10 to 50 nm, which can interact with the surface proteins of bacteriophages, physically capture and inactivate bacteriophages. In addition, nickel nanoparticles can produce reactive oxygen species (ROS) with a concentration of 5 to 20 μM through oxidative stress, further destroying the shell and genome structure of the bacteriophage, reducing the activity of the bacteriophage, thereby effectively inhibiting the horizontal transfer of resistance genes and reducing the risk of resistance gene spread. In the reactor to which the nitrogen-doped carbon nanofiber-anchored nickel nanoparticles of the present invention were added, the total content of multiple resistance genes such as sul2, tetW, tetA, and macB was reduced by 8.18% to 19.10% compared with the blank control group. Horizontal gene transfer experiments and qPCR detection further showed that the abundance of resistance genes of phages decreased by 27.8 to 47.2% after treatment with the modified material, and the gene horizontal transfer rate was significantly reduced.
[0019] (3) Changes in extracellular polymers in sludge: After 35 days of anaerobic digestion of sludge, the conductive material of the present invention was added, and the extracellular polymers in the sludge were extracted by thermal extraction, and the Fourier transform infrared spectroscopy was used to analyze the 1600-1700 cm -1The results showed that the α-helix of the sludge protein in the reactor was reduced by 17.3% to -29.1% compared with the α-helix of the sludge protein in the blank control group without addition, indicating that the addition of nitrogen-doped nanofibers anchored with nickel nanoparticles can loosen the secondary structure of the protein, and the COD content in the liquid phase was significantly increased, indicating that the conductive material further promoted the lysis and hydrolysis of the sludge, thereby promoting the hydrolysis process of the sludge. Three-dimensional fluorescence spectral analysis showed that the fluorescence area integral values of Region Ⅳ and Region V representing humic acid substances in the reactor were reduced by 12.85% to 21.31% compared with the blank control group without addition, and the content of humic acid substances in the sludge extracellular polymers was significantly reduced, indicating that the addition of conductive materials can promote the decomposition and transformation of difficult-to-degrade substances in the sludge and improve the biodegradability of the fermentation liquid.
[0020] (4) Promote methane production and organic matter degradation: After adding the conductive material of the present invention to a high-solid sludge anaerobic digestion reactor, the average COD degradation rate of the reactor with nanoparticles added increased by 34.22% compared to the reactor without nanoparticles. The cumulative methane production and maximum production rate increased by 25.66% and 28.21%, respectively. The addition of the material significantly increased the sludge hydrolysis rate, the organic matter degradation rate and the methane production rate in the anaerobic digestion reactor. At the same time, after the sludge is anaerobic treated, the nitrogen-doped nanofiber-anchored nickel nanoparticles therein can be recovered after magnet adsorption and ultrapure water washing. The saturation magnetization intensity of the recovered conductive material is as high as 117.21A·m 2 / kg, can be reused. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope photograph of the nitrogen-doped nanofibers anchored with nickel nanoparticles prepared in step 3 of Example 1;
[0022] Figure 2 The cumulative methane production and maximum methane production rate of the conductive material added group and the blank control group in Example 1 are shown;
[0023] Figure 3 This is a graph of functional enzyme activity after treatment with high-solid sludge in the conductive material-added group and the blank control group in Example 1;
[0024] Figure 4 It is a diagram showing the types and contents of sludge resistance genes in the conductive material added group and the blank control group after the high solid content sludge treatment in Example 1;
[0025] Figure 5 is a graph showing the change in the number of bacteriophages in sludge after treatment with high-solid sludge in the conductive material-added group and the blank control group in Example 1;
[0026] Figure 6This is a graph showing the changes in the number of cytochrome-related genes encoded in the sludge after the high-solid sludge treatment of the conductive material addition group and the blank control group in Example 1. DETAILED DESCRIPTION
[0027] The beneficial effects of the present invention are verified by the following examples.
[0028] Example 1: The method of using nitrogen-doped nanofibers to anchor nickel nanoparticles to enhance anaerobic methanogenesis in high-solid sludge and reduce sludge resistance genes is carried out in the following steps:
[0029] 1. Prepare nickel nanoparticle precursor by sol-gel method: dissolve 25 g nickel nitrate hexahydrate (Ni(NO3)2·6H2O) in a mixed solution of 50 mL ethanol and 150 mL water, add ammonia water to adjust the pH value to 10, stir for 1 hour to perform hydrolysis reaction to generate uniformly dispersed sol particles, and then stand for 5 hours to obtain nano nickel precursor by spontaneous gelation;
[0030] 2. Prepare a 15% polyacrylonitrile solution with 10 mL of N,N-dimethylformamide (DMF) as solvent, and evenly disperse the nano-nickel precursor prepared in step 1 in the polyacrylonitrile solution to obtain an electrospinning solution; add the electrospinning solution to an electrospinning machine, set the voltage of the electrospinning machine to 20 kV, and the solution injection speed to 1.5 mL·h -1 , the humidity is 30%, and the distance between the shaft rollers is 20 cm to perform electrospinning to obtain primary nanofibers; then the primary nanofibers are peeled off from the aluminum foil, placed in a vacuum drying oven at a temperature of 80° C. and vacuum dried for 12 hours to remove the residual organic solvent, and the nanofibers containing the nickel precursor are obtained;
[0031] 3. Place the nanofibers containing nickel precursor in a high temperature tube furnace at 15 °C min -1 The heating rate was raised to 400℃ and kept at that temperature for 1h, and then the temperature was raised at 10℃ min -1 The heating rate was continued to increase to 900°C and kept for 2 h, and finally cooled to room temperature to obtain nitrogen-doped nanofiber-anchored nickel nanoparticles;
[0032] 4. The residual sludge was taken from the return sludge of the secondary sedimentation tank of a municipal sewage treatment plant in Harbin. The residual sludge was centrifuged and stored in a refrigerator at 4°C. The supernatant was discharged and concentrated before use to make the solid content of the residual sludge 20% by mass percentage, which was used as high-solid sludge. The inoculated anaerobic sludge was taken from the semi-continuous reactor for anaerobic digestion of sludge in continuous operation in the laboratory. The operating temperature of the reactor was 37°C and the hydraulic retention time was 30 days. The main microorganisms in the inoculated anaerobic sludge were identified as Methanothrix, Methanobacterium and Methanolinea, among which the abundance of Methanothrix by mass percentage was 41.27%, the abundance of Methanobacterium by mass percentage was 18.82%, and the abundance of Methanolinea by mass percentage was 16.48%.
[0033] Two groups of reactors were set up, and 650mL of high-solid sludge was added to two identical anaerobic bottles with an effective volume of 1000mL, and then 150mL of inoculated anaerobic sludge was added to each of them; one group was added with 120mg of nitrogen-doped nanofiber-anchored nickel nanoparticles as the experimental group, and the other group was not added with nanoparticles as the blank control group, and the other designs were exactly the same; the headspace volume of the anaerobic bottle was 200mL; nitrogen with a purity of >99% was continuously introduced into the anaerobic bottle to remove the mixed oxygen in the system, and then the anaerobic bottle was sealed with a rubber stopper, and then the anaerobic bottle was placed in a constant temperature shaker at 37℃ and rotated at 150rpm. A 200mL air bag was connected to the outside of the anaerobic bottle to collect the generated biogas. The high-solid sludge was treated for 30 days, and various tests were carried out during the treatment process.
[0034] The scanning electron microscope (SEM) photograph of the nitrogen-doped nanofibers anchored with nickel nanoparticles prepared in step 3 of this embodiment is shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the nickel nanoparticles formed by the sol-gel method are anchored on the fibers, have a fiber spiral winding structure and a large surface area, which is conducive to the attachment and growth of microorganisms. The nickel nanoparticles are evenly distributed, and the size of the nickel nanoparticles is 10-100nm, which can not only improve the conductivity and activity of the conductive material, but also enhance its ability to transfer electrons between microorganisms during anaerobic digestion, thereby increasing the rate of methane production in the anaerobic process. The surface of the nitrogen-doped nanofiber-anchored nickel nanoparticles contains a variety of functional groups, which can promote the extracellular electron transfer of bacteria.
[0035] After 30 days of treatment with high-solid sludge in the anaerobic bottle, the conductivity of the anaerobic sludge in the two groups of reactors was tested. The results showed that after adding nitrogen-doped carbon nanofibers anchored with nickel nanoparticles, the conductivity of the anaerobic sludge increased by 31.58% compared with the blank control group without adding nanoparticles, and promoted the secretion of extracellular polymers (EPS). The content of EPS increased by 29.23%. The increase in EPS content can improve the flocculation strength of anaerobic granular sludge and the electron transfer capacity between anaerobic microorganisms.
[0036] After 30 days of treatment of high-solid sludge in the anaerobic bottle, the mycelial abundance of the anaerobic sludge in the two groups of reactors was tested. The results showed that the addition of nitrogen-doped carbon nanofibers anchored with nickel nanoparticles promoted the increase in the abundance of hydrogen-producing and acetic acid-producing bacteria Methanothrix in the anaerobic reactor, which increased by 12.52% compared with the control anaerobic reactor without the addition of nanoparticles, while the abundance of Methanolinea decreased by 6.37%. This result shows that the addition of nitrogen-doped carbon nanofibers anchored with nickel nanoparticles promoted the growth and metabolism of acetic acid fermentation methanogens and microorganisms that can directly transfer electrons, thereby indirectly improving the interspecies electron transfer efficiency of microorganisms, and then promoting the increase of methane yield in anaerobic digestion of sludge.
[0037] The volume of the biogas in the gas bag of Example 1 was measured every 3 days, and the gas composition was measured by gas chromatography (GC-7890A). The cumulative methane production and the maximum methane production rate of the blank control group and Example 1 were as follows: Figure 2 As shown, Figure 2 The results showed that the cumulative methane production of the blank control group was 178.87 mL / gVS, and the maximum methane production rate was 10.81 mL / d / gVS. The cumulative methane production of the reactor with nitrogen-doped nanofiber-anchored nickel nanoparticles was 224.77 mL / gVS, and the maximum methane production rate was 13.86 mL / d / gVS. The cumulative methane production of the reactor with nitrogen-doped nanofiber-anchored nickel nanoparticles increased by 25.66% compared with the blank control group, the maximum methane production rate increased by 28.21%, and the average COD degradation rate increased by 34.22%.
[0038] After the high-solid sludge in the anaerobic bottle was treated for 30 days, 10 mL of sludge was sampled from the bottom, middle and top of the reactor, and mixed evenly as the sludge samples to be tested for functional enzyme activity. The functional enzyme activities of the blank control group and Example 1 were as follows: Figure 3 As shown, Figure 3The results showed that compared with the blank control group, the activities of functional enzymes such as protease, α-glycosidase, acetate kinase, methanogenic coenzyme F420, and F430 were significantly improved in the reactor with nitrogen-doped nanofibers anchored with nickel nanoparticles. Compared with the blank control group, the activities of protease, α-glycosidase, acetate kinase, methanogenic coenzyme F420, and coenzyme F430 in the conductive material group of Example 1 increased by 15.25%, 12.46%, 17.91%, 22.32%, and 26.47%, respectively. After adding nitrogen-doped carbon nanofibers anchored with nickel nanoparticles, Ni was detected in the fermentation broth. + Ni is an essential element for the synthesis of coenzyme F420 and coenzyme F430 by microorganisms. + The increase in content indicates that the conductive material can release Ni + Promote the synthesis of related functional enzymes, thereby improving the conversion efficiency of organic matter.
[0039] After 30 days of high-solid sludge treatment in the anaerobic bottle, the anaerobic digestion liquid samples were collected, and the fermentation liquid components after centrifugation were analyzed by combining three-dimensional fluorescence spectroscopy, fluorescence regional integration and parallel factor analysis technology. The results showed that the fluorescence regional integration values of Region Ⅳ and Region V representing humic acid substances in the reactor with nitrogen-doped nanofibers anchored nickel nanoparticles were significantly reduced compared with the blank control group without addition. The fermentation liquid was dried and analyzed by Fourier infrared spectroscopy and circular dichroism spectroscopy. The results showed that the α-helix in the reactor with the addition of conductive materials was significantly reduced, indicating that the addition of nitrogen-doped nanofibers anchored nickel nanoparticles can make the protein structure loose.
[0040] After 30 days of treatment with high-solid sludge in the anaerobic bottle, the sludge after anaerobic digestion was centrifuged at 12000rpm for 10min, and DNA was extracted from the centrifuged sludge. Metagenomic sequencing technology was used to analyze the types and contents of sludge resistance genes. The types and contents of sludge resistance genes after high-solid sludge treatment in the conductive material group and the blank control group are shown in the figure. Figure 4 As shown, from Figure 4 It can be seen that in the reactor with nitrogen-doped carbon nanofibers anchored with nickel nanoparticles, the total content of multiple resistance genes such as sul2, tetW, tetA, and macB decreased by 8.18% to 19.10% compared with the blank control group.
[0041] qPCR was used to detect the changes in the number of bacteriophages in the sludge after the high-solid sludge treatment in the conductive material addition group and the blank control group in Example 1. The obtained phage number changes are shown in the figure below: Figure 5As shown, the number of resistance genes of the phage in the group with added conductive material in Example 1 decreased by 31.2% after treatment, and the gene horizontal transfer rate was significantly reduced. Nucleic acid leakage and protein denaturation analysis showed that the conductive material effectively destroyed the shell and genome structure of the phage.
[0042] Figure 6 This is a graph showing the changes in the number of cytochrome-related genes encoded by the sludge after the high-solid sludge treatment in the conductive material addition group and the blank control group in Example 1. Figure 6 It can be seen that the cytochrome-related genes (cyt, c-type, b-type, d-type) encoded in the sludge with the addition of nitrogen-doped nanofibers anchored nickel nanoparticles of this example increased by 15.2%, 12.9%, 23.8%, and 42.1% respectively compared with the group without addition, indicating that nitrogen-doped nanofibers anchored nickel nanoparticles can enhance the electron transfer ability between microorganisms.
[0043] The conductive material was separated from the treated sludge using high gradient magnetic separation technology and immersed in a 60% ethanol solution to remove organic matter and inorganic salts attached to the surface. After washing with ultrapure water three times, it was vacuum dried at 40°C for 24 hours to remove the remaining water in the washed doped carbon nanofiber anchored nickel nanoparticles. The saturation magnetization of the conductive material, nitrogen-doped carbon nanofiber anchored nickel nanoparticles, was tested to be 117.21A·m 2 / kg.
[0044] The recovered and cleaned nitrogen-doped carbon nanofiber anchored nickel nanoparticles were reused and added back into the residual sludge anaerobic digestion reactor. After 30 days of medium-temperature fermentation, the cumulative methane production increased by 12.78%, and the maximum methane production rate increased by 8.21% compared with the control group without adding conductive materials, showing good separation, recovery and reuse performance.
[0045] Example 1 proves that nitrogen-doped and nickel nanoparticle surface-modified materials can significantly inhibit the activity of bacteriophages and the risk of resistance gene spread through multiple mechanisms such as capture, inactivation, induction of oxidative stress and genome destruction.
Claims
1. A method for enhancing anaerobic methanogenesis in high-solid sludge and reducing sludge resistance genes by using nitrogen-doped nanofibers anchored with nickel nanoparticles, characterized in that The method proceeds as follows:
1. Prepare nickel nanoparticle precursor by sol-gel method: dissolve nickel nitrate hexahydrate in a mixed solution of ethanol and water, add ammonia water to adjust the pH value to 9-11, stir at 100-120 rpm for 0.5-1 hour to hydrolyze to generate uniformly dispersed sol particles, and then stand for 4-6 hours to obtain nano nickel precursor by spontaneous gelation; 2. Evenly dispersing the nano nickel precursor in a polyacrylonitrile solution with a mass percentage concentration of 10% to 16% and N,N-dimethylformamide as a solvent to obtain an electrospinning solution; adding the electrospinning solution to an electrospinning machine for electrospinning to obtain primary nanofibers; and vacuum drying the primary nanofibers to obtain nanofibers containing a nickel precursor; 3. Place the nanofibers containing nickel precursor in a high temperature tube furnace at 10-15°C min -1 The heating rate is raised to 400-420℃ and kept at this temperature for 1-1.5h, then increased to 10-15℃ min -1 The heating rate is continued to be increased to 900-950°C and kept for 2-2.5 hours, and finally cooled to room temperature to obtain nitrogen-doped nanofiber-anchored nickel nanoparticles; 4. Add high-solid sludge into an anaerobic digestion reactor, then inoculate anaerobic sludge, and then add nitrogen-doped nanofiber-anchored nickel nanoparticles; the headspace volume of the reactor is 20% to 25% of the effective volume of the reactor, and the amount of nitrogen-doped nanofiber-anchored nickel nanoparticles added is 5% to 12% of the dry weight of the high-solid sludge; nitrogen is continuously introduced into the anaerobic digestion reactor to remove mixed oxygen in the system, and then the anaerobic digestion reactor is operated at a temperature of 35 to 38°C, and the hydraulic retention time of the high-solid sludge in the anaerobic digestion reactor is 30 to 35 days, thereby completing the anaerobic methanogenesis of the high-solid sludge and the reduction of sludge resistance genes.
2. The method of using nitrogen-doped nanofibers anchored with nickel nanoparticles to enhance anaerobic methanogenesis in high-solid sludge and reduce sludge resistance genes according to claim 1, characterized in that: For the electrospinning described in step 2, the voltage of the electrospinning machine is 20 kV and the solution injection speed is 1.5 mL·h -1 , humidity is 25% to 30%, and the distance between the shaft rollers is 20cm.
3. The method for enhancing anaerobic methanogenesis in high-solid sludge and reducing sludge resistance genes by using nitrogen-doped nanofibers anchored with nickel nanoparticles according to claim 1 or 2, characterized in that: The vacuum drying described in step 2 is drying under vacuum conditions at a temperature of 70 to 80° C. for 10 to 12 hours.
4. The method for enhancing anaerobic methanogenesis in high-solid sludge and reducing sludge resistance genes by using nitrogen-doped nanofibers anchored with nickel nanoparticles according to claim 1 or 2, characterized in that: The high-solid sludge described in step 4 has a solid content of 16% to 20% by mass.
5. The method for enhancing anaerobic methanogenesis in high-solid sludge and reducing sludge resistance genes by using nitrogen-doped nanofibers anchored with nickel nanoparticles according to claim 1 or 2, characterized in that: The main microorganisms in the anaerobic sludge described in step 4 are Methanothrix, Methanobacterium and Methanolinea.
6. The method for enhancing anaerobic methanogenesis in high-solid sludge and reducing sludge resistance genes by using nitrogen-doped nanofibers anchored with nickel nanoparticles according to claim 1 or 2, characterized in that: The size of the nitrogen-doped nanofiber-anchored nickel nanoparticles prepared in step 3 is 10 to 100 nm.
7. The method for enhancing anaerobic methanogenesis in high-solid sludge and reducing sludge resistance genes by using nitrogen-doped nanofibers anchored with nickel nanoparticles according to claim 1 or 2, characterized in that: The amount of doped nanofiber-anchored nickel nanoparticles added in step four is 10% to 12% of the dry weight of high-solid sludge; under such conditions, the fluorescence area integral values of Region IV and Region V representing humic acid substances in the reactor are reduced by 12.85% to 21.31% compared with the blank control group without addition, indicating that the material can improve the biodegradability of the fermentation broth.
8. The method for enhancing anaerobic methanogenesis in high-solid sludge and reducing sludge resistance genes by using nitrogen-doped nanofibers anchored with nickel nanoparticles according to claim 1 or 2, characterized in that: The amount of the doped nanofiber-anchored nickel nanoparticles added in step 4 is 8% to 10% of the dry weight of the high-solid sludge; under such conditions, after 35 days of anaerobic digestion of the sludge, the sludge extracellular polymers are extracted by thermal extraction, and the Fourier transform infrared spectroscopy is used to analyze the 1600-1700cm -1 The test showed that the α-helix of the sludge protein in the reactor was reduced by 17.3%-29.1% compared with the α-helix of the sludge protein in the blank control group without addition, indicating that the addition of nitrogen-doped nanofibers anchored nickel nanoparticles can loosen the protein structure and promote the hydrolysis process of the sludge.
9. The method of using nitrogen-doped nanofibers anchored with nickel nanoparticles to enhance anaerobic methanogenesis in high-solid sludge and reduce sludge resistance genes according to claim 1, characterized in that: The amount of the doped nanofiber anchored nickel nanoparticles added in step 4 is 10% to 12% of the dry weight of the high-solid sludge; after the anaerobic digestion of the sludge is completed, the doped nanofiber anchored nickel nanoparticles are adsorbed by a magnet and washed with water to obtain liquid nitrogen doped carbon nanofiber anchored nickel nanoparticles with a saturation magnetization of 117.21A·m 2 / kg.
10. The method of using nitrogen-doped nanofibers anchored with nickel nanoparticles to enhance anaerobic methanogenesis in high-solid sludge and reduce sludge resistance genes according to claim 1, characterized in that: After the anaerobic digestion treatment of the sludge described in step 4 is completed, the conductivity of the sludge is increased by 18.1% to 33.9% compared with the blank control group without addition, and the abundance of cytochrome-related genes cyt, c-type, b-type, and d-type in the sludge is increased by 12.9% to 42.1%, indicating that nitrogen-doped nanofibers anchored nickel nanoparticles enhance the ability of electron transfer between microorganisms.
Citation Information
Patent Citations
Method for promoting anaerobic digestion process and improving methane production efficiency by CNTs-Ni-Fe3O4
CN110330200A
Carbon nanofiber loaded monatomic nickel catalyst as well as preparation method and application thereof
CN116850997A
Method for promoting high-temperature anaerobic digestion of sludge to produce methane
CN117003455A
Application of nitrogen-doped carbon nanofiber membrane for anchoring superfine Fe-Mn bimetallic nanoparticles to flow-through electro-Fenton degradation of organic pollutants
CN118892859A
Accelerated start-up of anaerobic reactors based on conductive nanomaterials
JP7046298B1